Mouse Abdominal Fat Depots Reduced by Butyric Acid-Producing Leuconostoc mesenteroides - John Jackson Yang; Minh Tan Pham; Adelia Riezka Rahim; Tsung-Hsien Chuang; Ming-Fa Hsieh; Chun-Ming Huang (Microorganisms, 2020)
The activation of peroxisome proliferator-activated rece ptor gamma (PPAR-γ) is known to induce the differentiation of adipocytes. This study aimed to investigate the probiotic effect of Leuconostoc mesenteroides (L. mesenteroides) on high-fat diet (HFD)-induced PPAR-γ activation and abdominal fat depots. Incubation of differentiated 3T3-L1 adipocytes with media of L. mesenteroides EH-1, a butyric acid-producing strain, significantly reduced the amounts of lipid droplets. The oral administration of L. mesenteroides EH-1 produced large amounts (>1 mM) of butyric acid in cecum and attenuated the HFD-induced upregulation of PPAR-γ and accumulation of abdominal fats in mice. The combination of 2% glucose with L. mesenteroides EH-1 increased the production of butyric acid and potentiated the probiotic activity of L. mesenteroides EH-1 against the formation of lipid droplets in 3T3-L1 adipocytes as well as abdominal fats in HFD-fed mice. The inhibition of free fatty acid receptor 2 (Ffar2) by its antagonist, GLPG-0974, markedly diminished the probiotic effects of L. mesenteroides EH-1 plus glucose on the suppression of HFD-induced PPAR-γ and abdominal fats. Besides demonstrating the probiotic value of L. mesenteroides EH-1, our results highlight the possible therapy targeting the butyric acid-activated Ffar2 pathway to reduce abdominal fats.